The Effectiveness of the Flipped Learning Method on the Subject of Electrical Technology 1 among Polytechnic Students with Different Learning Styles - Madar, Ahmad Rizal; Mustafa, Mohamad Zaid; Hamid, Hashima; A.Jalil, Noor Azyani; Amiruddin, Mohd Hasril; Abdullah, Nurhanim Saadah (2024)
The preliminary study findings found that Electrical Technology 1 (DET 1013) is a subject that always has a meager percentage of students who pass with distinction, while the percentage of students who fail is high. Students face problems in imagining the learning content delivered by the lecturer. Blended learning is a combination of traditional and technological methods. Among the blended learning methods that are usually used is flipped learning. The research aim is to identify the effectiveness of the flipped learning method on electrical technology 1 among students with different learning styles. This study uses a quasi-experimental method with a non-equivalent group pre-post test design. The research sample selected uses the purposive sampling method. Before and after flipped learning was implemented, questionnaires about interest contained 30 items about interest in Electrical Technology 1 subject, given to students in the treatment and control group. The analysis used is MANCOVA, using the SPSS software version 25. The analysis results show that there is a difference between before the start of the learning session and after the learning session. Therefore, the flipped learning method can help students who have different learning styles. Indirectly increases their academic achievement and interest in Electrical Technology 1. Besides, can instill elements of active student involvement in selfdevelopment and motivation to build the strengthening basis of their thinking and memory systems.